Analisis Urgensi Database Perancangan Sistem Informasi PT PSL Dengan Fishbone Diagram dan Diagram Pareto - Fasha, Adinda; Nenden Kostini; Tribowo Rachmat Fauzan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
In the era of technology and increasingly tight logistics industry competition, the speed and accuracy of distribution services are very important to maintain the company's competitiveness. Various reasons, including the lack of digitization of motor vehicle delay recording (KBM) as the company's distribution key. The purpose of this study is to identify the factors that cause these delays and to determine how important database development is to build an efficient logistics information system. This study uses a Pareto diagram based on the 80/20 principle to determine the most important factors causing obstacles and Fishbone Diagram analysis to map the causal factors in a structured manner. The results of the analysis show that more than 80% of distribution delays are caused by KBM problems, operational problems, and road conditions. Additionally, the Fishbone diagram analysis indicates that engine factors (KBM) and operational policies are the two primary causes requiring special attention. This further strengthens the fact that creating a comprehensive and accurate database is very important as a basis for designing PT PSL's logistics information system.